A high insulation filled high thermal conductivity epoxy resin composite material and its preparation method and application

By introducing boron nitride, alumina and polyimide into the epoxy resin composite, the problem of deterioration of the insulation performance of the existing high-content fill-type thermally conductive epoxy resin is solved, and the preparation of high-insulating and high-thermal conductive composite materials is realized , suitable for packaging materials for new energy vehicle drive motors.

CN118496622BActive Publication Date: 2025-02-18HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410638290.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The insulation performance of existing high-content fill-type thermally conductive epoxy resins is deteriorated, and the composite material preparation process is complex and costly, which affects the normal operation and safety of the drive motor of new energy vehicles.

Method used

By mixing boron nitride, alumina and epoxy resin, combining polyimide (PI) as the filling item, vacuum stirring box blending and flat vulcanizer curing process, high-insulating fill type high-thermal conductivity epoxy resin composite material is prepared by using vacuum stirring box blending and flat vulcanizer curing technology, a high-insulating fill type high-thermal conductivity epoxy resin composite material is prepared by combining boron nitride, alumina and epoxy resin, combined with polyimide (PI) as the filling item, and using vacuum stirrer box blending and flat vulcanizer curing technology, a high-insulating fill type high-thermal conductivity epoxy resin composite material is prepared by using the following methods: .

Benefits of technology

The insulation performance of composite materials is significantly improved, the breakdown field strength is increased by 83.92%, and the volume resistivity is increased by 96.54%, while maintaining high thermal conductivity. It is suitable for thermally conductive packaging insulation materials for new energy vehicle drive motors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496622B_ABST
    Figure CN118496622B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-insulation filled high-thermal-conductivity epoxy resin composite material, a preparation method and an application thereof, and belongs to the technical field of thermally conductive insulating composite materials and their preparation. The present invention solves the problem of deterioration of the insulation performance of existing high-content filled thermally conductive epoxy resins. The present invention uses epoxy resin doped with boron nitride and aluminum oxide as precursors, adds insulating medium PI to the precursor, and obtains a high-insulation filled thermally conductive epoxy resin composite material through high-temperature curing. The high-insulation filled high-thermal-conductivity epoxy resin composite material prepared by the present invention has a breakdown field strength of 219.9 kV / mm and a volume resistivity of 3.57×10 16 Ω·m, thermal conductivity is 1.918W / m·K, and it is expected to be used as a thermally conductive packaging insulation material for new energy drive motors. In addition, the preparation method provided by the present invention has low cost, is easy to implement, has good environmental protection, and the operation of the required instruments is simple and safe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-insulation filled high-thermal-conductivity epoxy resin composite material and a preparation method and application thereof, belonging to the technical field of thermal-conductive insulating composite materials and preparation thereof. Background Art

[0002] As the main direction of future automobile development, the electric drive and electric control systems of new energy vehicles directly affect the power, energy efficiency and reliability of the vehicle. Insulation materials are a key part of the electric drive and electric control systems, and directly determine the power density, efficiency and reliability of the motor. Therefore, the development of high-performance insulation materials suitable for new energy vehicle drive motors has important practical significance and strategic value.

[0003] Epoxy resin (EP) packaging material is a key material for packaging the windings of new energy vehicle drive motors. It is mainly used in motor windings, cable terminals, motor packaging and other fields. However, as the requirements for motor packaging become more stringent, the drive motor urgently needs to solve the heat dissipation problem. At present, high thermal conductivity potting glue is filled with high-content and high-thermal conductivity ceramic fillers to solve the problem of poor thermal conductivity; but with the increase of the content of thermal conductive fillers, the insulation performance of the material cracks. If it is not solved in time, it will greatly affect the normal operation of the drive motor and cause safety hazards. Therefore, improving the insulation performance of filled high thermal conductivity epoxy resin composite materials has become a key factor in improving the working performance of the drive motor. Summary of the invention

[0004] In order to solve the problems of deterioration of insulation performance of existing high-content filled thermally conductive epoxy resins, complexity and high cost of composite material preparation process, the present invention provides a high-insulation filled high-thermal conductive epoxy resin composite material and its preparation method and application.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a method for preparing a high-insulation filled high-thermal-conductivity epoxy resin composite material, the method comprising the following steps:

[0007] (1) mixing boron nitride, aluminum oxide and epoxy resin to obtain a precursor;

[0008] (2) Using PMDA and ODA as raw materials and DMAC as solvent, PI glue was obtained by in situ polymerization;

[0009] (3) adding the precursor obtained in (1) to the PI glue obtained in (2), stirring to obtain a glue to be cured, and obtaining a high-insulation filled thermally conductive epoxy resin composite material after curing.

[0010] It is further defined that in (1), the particle size of the boron nitride is 30-35 μm; and the particle size of the aluminum oxide is 5-7 μm.

[0011] It is further defined that in (1), the mass of the boron nitride accounts for 30 wt % of the mass of the epoxy resin; and the mass of the aluminum oxide accounts for 50 wt % of the mass of the boron nitride.

[0012] It is further defined that the epoxy resin in (1) is a mixture of AG70 and F51 in a mass ratio of 1:1.

[0013] It is further defined that the molar ratio of PMDA to ODA in (2) is 1:1.02.

[0014] It is further defined that the in situ polymerization reaction conditions in (2) are: stirring the reaction for 12 hours under vacuum conditions.

[0015] It is further defined that (3) the mass of PI in the adhesive to be cured is 2-6 wt % of the mass of the epoxy resin.

[0016] It is further defined that the curing process in (3) is: keeping at 180°C for 3 hours, heating to 200°C and keeping for 2 hours.

[0017] The second object of the present invention is to provide a high-insulation filled high-thermal conductivity epoxy resin composite material prepared by the above method.

[0018] The third object of the present invention is to provide an application of the above-mentioned high-insulation filled high-thermal conductivity epoxy resin composite material, specifically used as a thermally conductive packaging insulation material for new energy vehicle drive motors.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention uses epoxy resin-based boron nitride and alumina as the matrix, uses polyimide (PI) with high insulation performance as the filler, blends the matrix and the filler in a vacuum stirring box, and cures at high temperature in a flat plate vulcanizer to obtain a high-insulation epoxy resin-based thermal conductive composite material. Among them, the breakdown field strength of the BN / Al2O3-EP / 4wt%PI composite material is 219.9kV / mm, which is 83.92% higher than that of the epoxy resin-based boron nitride and alumina matrix (119.56kV / mm), and the volume resistivity is 3.57×10 16 Ω·m, compared with epoxy resin-based boron nitride and alumina matrix (3.66×10 14 The thermal conductivity of the material is 1.918W / m·K.

[0021] (2) The present invention provides a preparation process for an insulating filled high thermal conductivity epoxy resin composite material with low cost, simple process, easy implementation, good environmental protection, and the operation of the instrument used is simple and safe. It provides an effective solution to the problem of poor insulation of epoxy resin used in drive motors and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the BN / Al2O3-EP / 2wt%PI high insulation filled high thermal conductivity epoxy resin composite material prepared in Example 1;

[0023] Figure 2 X-ray diffraction diagrams of the high-insulation filled high-thermal-conductivity epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Example 1;

[0024] Figure 3 A comparison chart of the breakdown field strength of the high-insulation filled high-thermal-conductivity epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Example 1;

[0025] Figure 4 This is a comparison chart of the volume resistivity of the high-insulation filled high-thermal-conductivity epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Example 1;

[0026] Figure 5 This is a comparison chart of the thermal conductivities of the high-insulation filled high-thermal-conductivity epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0031] Example 1

[0032] The method for preparing a high-insulation filled high-thermal-conductivity epoxy resin composite material in this embodiment comprises the following steps:

[0033] Step 1, weighing boron nitride (BN) and aluminum oxide (Al2O3) in a certain mass ratio and mixing them with epoxy resin in a vacuum stirring box to obtain a precursor;

[0034] Specifically, the size of boron nitride (BN) is 30-35 μm, the size of aluminum oxide (Al2O3) is 5-7 μm, the mass of boron nitride accounts for 30 wt% of the mass of epoxy resin, the mass of aluminum oxide accounts for 50 wt% of the mass of boron nitride, and the stirring time is 6 hours.

[0035] Step 2, adding 4,4′-diaminodiphenyl ether (ODA) into an organic solvent N,N-dimethylacetamide solution (DMAC), stirring to completely dissolve it; adding phthalic anhydride monomer (PMDA), and causing a polymerization reaction under vacuum conditions to obtain a polyimide prepolymer insulating medium (PI);

[0036] Specifically, in order to fully react the dianhydride with the diamine, the molar ratio of 4,4′-diaminodiphenyl ether (ODA) to phthalic anhydride monomer (PMDA) is 1:1.02, and the reaction time of 4,4′-diaminodiphenyl ether (ODA) and phthalic anhydride monomer (PMDA) in a vacuum oven is 12 hours.

[0037] Step 3, pour the polyimide prepolymer insulating medium (PI) obtained in step 2 into the precursor obtained in step 1, stir in a vacuum stirring box to obtain a blend, pour the blend into a mold, and cure it in a flat vulcanizer to obtain a composite material, named BN / Al2O3-EP / 2wt%PI.

[0038] Specifically, the mass of PI in the blend is ensured to be 2 wt % of the mass of the epoxy resin, the stirring time in the vacuum stirring box is 6 h, and the curing process is 180° C. for 3 h and 200° C. for 2 h.

[0039] The structure and performance of the BN / Al2O3-EP / 2wt%PI composite material obtained in this example were characterized, and the results are as follows:

[0040] (1) The thickness of the BN / Al2O3-EP / 2wt%PI composite material obtained in this example was measured. The results showed that the thickness was 80-120 μm.

[0041] (2) The microstructure of the BN / Al2O3-EP / 2wt%PI composite material obtained in this example was characterized. Figure 1 As shown by Figure 1It can be seen that the BN / Al2O3-EP / 2wt%PI composite material is evenly distributed and continuous, and the interface compatibility is good, which proves that the preparation of the BN / Al2O3-EP / 2wt%PI composite material is successful.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the mass of PI in the blend obtained in step 3 is 4wt% of the mass of epoxy resin, and the rest of the operation process and parameter settings are the same as those in embodiment 1. The composite material obtained in this embodiment is named BN / Al2O3-EP / 4wt%PI.

[0044] Example 3

[0045] The difference between this embodiment and embodiment 1 is that the mass of PI in the blend obtained in step 3 is 6wt% of the mass of epoxy resin, and the rest of the operation process and parameter settings are the same as those in embodiment 1. The composite material obtained in this embodiment is named BN / Al2O3-EP / 6wt%PI.

[0046] Comparative Example 1

[0047] The difference between this embodiment and embodiment 1 is that the mass of PI in the blend obtained in step 3 is 0wt% of the mass of epoxy resin, and the rest of the operation process and parameter settings are the same as those in embodiment 1. The composite material obtained in this embodiment is named BN / Al2O3-EP.

[0048] Effect example

[0049] The performance of BN / Al2O3-EP / 2wt%PI, BN / Al2O3-EP / 4wt%PI, BN / Al2O3-EP / 6wt%PI prepared in Examples 1 to 3 and BN / Al2O3-EP prepared in Comparative Example 1 were characterized and compared, and the results are as follows:

[0050] (1) X-ray diffraction patterns of BN / Al2O3-EP / 2wt%PI, BN / Al2O3-EP / 4wt%PI, BN / Al2O3-EP / 6wt%PI prepared in Examples 1 to 3 and BN / Al2O3-EP prepared in Comparative Example 1, as well as the raw materials BN and Al2O3 are shown in Figure 2. Figure 2 As shown by Figure 2It can be seen that the characteristic diffraction peak of BN / Al2O3-EP / PI composite material appears at 2θ=26.745°, and 41.614° corresponds to the (002)(100) crystal plane of BN, which corresponds to the standard card (01-073-2095); the characteristic diffraction peaks appear at 43°, 35°, 58°, 26°, 38° and 53°, corresponding to the (113), (104), (116), (012), (110) and (024) crystal planes of Al2O3; since EP belongs to the amorphous state, its characteristic diffraction peak is "steamed bun-shaped" and appears near 2θ=10°-20°; due to the low content of PI, the peak value is relatively low, and the characteristic peak coincides with the characteristic peak of epoxy resin, and the characterization is not obvious.

[0051] (2) The breakdown field strength test was performed on BN / Al2O3-EP / 2wt%PI, BN / Al2O3-EP / 4wt%PI, BN / Al2O3-EP / 6wt%PI prepared in Examples 1 to 3 and BN / Al2O3-EP prepared in Comparative Example 1. The results are as follows: Figure 3 As shown by Figure 3 It can be seen that the introduction of PI into BN / Al2O3-EP will greatly increase its breakdown field strength. The maximum breakdown field strength of the BN / Al2O3-EP / 4wt%PI composite material can reach 219.9KV / mm.

[0052] (3) The volume resistivity of BN / Al2O3-EP / 2wt%PI, BN / Al2O3-EP / 4wt%PI, BN / Al2O3-EP / 6wt%PI prepared in Examples 1 to 3 and BN / Al2O3-EP prepared in Comparative Example 1 were characterized. The changes in volume resistivity are shown in FIG. Figure 4 As shown in the figure, it can be seen that the introduction of PI into BN / Al2O3-EP will greatly increase the volume resistivity, among which the volume resistivity of BN / Al2O3-EP / 4wt%PI composite material can reach a maximum of 3.57×10 16 , which is consistent with the variation law of breakdown field strength. The results show that the BN / Al2O3-EP / PI composite material prepared by the method provided by the present invention still has a certain insulation level at high frequency.

[0053] (4) The thermal conductivity of BN / Al2O3-EP / 2wt%PI, BN / Al2O3-EP / 4wt%PI, BN / Al2O3-EP / 6wt%PI prepared in Examples 1 to 3 and BN / Al2O3-EP prepared in Comparative Example 1 were tested. The results are as follows: Figure 5 As shown by Figure 5It can be seen that the introduction of PI will cause the thermal conductivity of the composite material to decrease to a certain extent, among which the thermal conductivity of the BN / Al2O3-EP / 2wt%PI composite material can reach up to 1.918W / m·K. The results show that although the introduction of PI causes a slight decrease in the thermal conductivity of the composite material, it still maintains a relatively high thermal conductivity level.

[0054] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high insulation filled high thermal conductivity epoxy resin composite material, characterized in that: include: (1) mixing boron nitride, aluminum oxide and epoxy resin to obtain a precursor; (1) The mass of boron nitride accounts for 30wt% of the mass of epoxy resin; the mass of aluminum oxide accounts for 50wt% of the mass of boron nitride; (2) Using PMDA and ODA as raw materials and DMAC as solvent, PI glue was obtained by in situ polymerization; (3) adding the precursor obtained in (1) to the PI glue obtained in (2), stirring to obtain a glue to be cured, and obtaining a high-insulation filled thermally conductive epoxy resin composite material after curing; (3) The curing process is: keep at 180℃ for 3h, then heat to 200℃ and keep for 2h; (3) The mass of PI in the adhesive to be cured is 2-6wt% of the mass of the epoxy resin.

2. The preparation method according to claim 1, characterized in that: (1) The particle size of boron nitride is 30-35 μm; the particle size of aluminum oxide is 5-7 μm.

3. The preparation method according to claim 1, characterized in that: (1) The epoxy resin is mixed with AG70 and F51 in a mass ratio of 1:

1.

4. The preparation method according to claim 1, characterized in that: The molar ratio of PMDA to ODA in (2) is 1:1.

02.

5. The preparation method according to claim 1, characterized in that: (2) The in-situ polymerization reaction conditions are: stirring the reaction for 12 hours under vacuum conditions.

6. A high insulation filled high thermal conductivity epoxy resin composite material prepared by the method according to any one of claims 1 to 5.

7. An application of the high insulation filled high thermal conductivity epoxy resin composite material according to claim 6, characterized in that: Used as thermally conductive packaging insulation material for new energy vehicle drive motors.

Citation Information

Patent Citations

  • Adhesive composition and adhesive sheet, and cured material and semiconductor device using same

    CN105026510A

  • Readily processable polyimide and preparation process of same

    US5268447A